A mixed-methods approach to develop and validate the Malaysia anti-hypertensive agents non-adherence scale among hypertensive patients in Kuala Lumpur, Malaysia - Yew, Sheng Qian (2022)
Existing scales used to measure non-adherence to anti-hypertensive medications are known to have various limitations—their psychometric properties were unsatisfactory and insufficiently assessed, they are lacking multi-dimensionality, lacking theoretical clarity, unable to comprehensively assess the themes of non-adherence to anti-hypertensive medications, and with uncertain cultural adaptation when administered in the local hypertensive populations. To address these limitations, the current study aimed to explore the themes of non-adherence to anti-hypertensive medications among hypertensive patients from health clinics in Kuala Lumpur, Malaysia. Such themes were used to develop a scale, named the Malaysia Anti-hypertensive Agent Non-Adherence Scale (MAANS). Also examined were the psychometric properties (factor structure, reliability, and predictive validity) of the MAANS. This was a two-phase exploratory mixed-methods study. In Study I (qualitative approach), hypertensive patients attending Kuala Lumpur Health Clinic and Cheras Baru Health Clinic were invited to participate in in-depth interviews. Themes of non-adherence reported by these patients were then used to generate initial items of the MAANS. An expert review was conducted to examine the content validity of the MAANS. In Study II (quantitative approach), data from 213 participants were subjected to exploratory factor analyses (EFA) to uncover the factor structure of the scale, thereby formed the modified version of the MAANS. Then, data from 205 participants were subjected to confirmatory factor analysis (CFA) to verify the factor structure of the modified version of the MAANS. Hence, the final version of the MAANS. Reliability of the final version of the MAANS was examined by Cronbach’s alpha coefficient. Meanwhile, the predictive validity was established using the WHO Quality of Life (QOL) BREF Malay version, which consists of Physical QOL, Psychosocial QOL, Social QOL, and Environmental QOL. Ten qualitative interviews were conducted and generated 73 items. Seven items was removed from the expert review. Based on the EFA, 21 items were retained in the modified version of the MAANS, which encompassed of five themes, namely, Perceived Non-Susceptibility, Poor Doctor-Patient Relationship, Unhealthy Lifestyle, Perceived Barriers, and Limitations of Healthcare Facilities. The modified version of the MAANS was subsequently subjected to CFA. When this was done, only three themes, namely, Perceived Non-Susceptibility, Poor Doctor-Patient Relationship, and Unhealthy Lifestyle were retained in the final version of the MAANS. The 14-item, 3-factor final version of the MAANS reported good model fit indices. Cronbach alpha was .64. Only Poor Doctor-Patient Relationship and Unhealthy Lifestyle themes of the final version of the MAANS were found to significantly predict Social QOL and Environment QOL. The final version of the MAANS has partial predictive validity as all of its themes were unable to predict Physical QOL and Psychosocial QOL. In conclusion, the MAANS is proven as a multidimensional, hypertension-specific, and locally derived scale. The scale was found to have moderate reliability and partial predictive validity. It is hoped that the MAANS can help to inform the future development of interventions to enhance patients’ adherence, thereby reducing the prevalence of uncontrolled hypertension.